Correction: Cai et al. Roles of Three FgPel Genes in the Development and Pathogenicity Regulation of Fusarium graminearum. J. Fungi 2024, 10, 666 - Lu Cai; Xiao Xu; Ye Dong; Yingying Jin; Younes M. Rashad; Dongfang Ma; Aiguo Gu (Journal of Fungi)
In the original article [...]